Post-fire behaviour and residual resistances of S700 high strength steel tubular section stub columns under combined loading - Zhong, Yukai (2022)
This paper reports experimental and numerical studies on the post-fire behaviour and residual resistances of S700 high strength steel tubular section stub columns under combined compression and bending. A testing programme was firstly performed, including heating and cooling of specimens as well as post-fire material testing, initial local geometric imperfection measurements and eccentric compression tests. The testing programme was followed by a numerical modelling programme, where finite element models were developed and validated against the test results and then employed to carry out parametric studies to generate further numerical data over a wide range of cross-section dimensions and loading combinations. Given that there are no design standards for high strength steel structures after exposure to fire, the design interaction curves for high strength steel tubular section stub columns under combined loading at ambient temperature, as given in the European code, American specification and Australian standard, were evaluated, using post-fire material properties, for their applicability to S700 high strength steel tubular section stub columns under combined loading after exposure to fire. The evaluation results revealed that all the three sets of codified design interaction curves yield overall accurate post-fire residual resistance predictions for S700 high strength steel tubular section stub columns under combined loading, with the highest level of design accuracy offered by the American specification.